Breast Cancer among Pakistani Women in Referral Hospitals: An Overview of Risk Factors - Saria, Maria Shabbir; Mirza, Masoom Raza; Habib, Lubna; Zubair, Muhammad (Ibrahim Medical College Journal, 2010)
The aim of this study was to determine the significance of various reproductive risk factors amongst Pakistani women suffering from breast carcinoma. This observational study was carried out from March 2007 to February 2009 at three hospitals. The women who presented with breast swelling with or without discharge from nipple were included in the study. The diagnosis of breast cancer was confirmed by histopathological examination. A questionnaire included history and various reproductive risk factors. The study patients were divided into two groups by their menopausal history – premenopausal and post-menopausal as ‘group A’ and ‘group B’, respectively. A total of 70 patients had the diagnosis of breast cancer. Of them, 32 were in group A and 38 in group B. Regarding age distribution, 49% were found in ≥51 years of age and 29% in the age group 30 – 40 years. The mean age at menarche was 13.3 years in group A and 12.4 years in group B. Nulliparity was seen in 12.5% cases in group A and 5.26% in group B. History of first full term pregnancy (FFTP) below the age of 20 was present in majority of cases in both groups though higher in group B. Breast cancer in post-menopausal women was exclusively found among those who had early menarche (<=11 years) and was more frequent among those who had FFTP below 20 years of age compared with the pre-menopausal group (88% vs. 66%). The study showed higher frequency of breast cancer in postmenopausal women having early menarche and also more frequent among those with early FFTP. Parity, breast feeding, oral contraceptive pill use were not related to breast cancer. Ibrahim Med. Coll. J. 2010; 4(1): 1-3 Indexing Words: Breast carcinoma; risk factors; genetics. DOI: 10.3329/imcj.v4i1.5926